2003
DOI: 10.1046/j.0266-4909.2002.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanisms through which computers contribute to learning

Abstract: Even though it has been established that the incorporation of computers into the teaching and learning process enhances student performance, the underlying mechanisms through which this is accomplished have been largely unexplored. The present study aims to shed light on this issue. Two groups of 10 secondary school students were tutored by their geography teacher in how to solve correlational problems. Students in the one group used paper and pencil while students in the other group used a computer spreadshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
0
17
0
6
Order By: Relevance
“…As in the Varnhagen and Digdon (2002) study, the number of accesses was unrelated to exam scores. This pattern of associations, along with students' favorable ratings of the practice exercises, suggests that it was not just exposure to the content of the tutorials that predicted learning but engaging with problems that required students to apply learned concepts (Karasavvidis, Pieters, & Plomp, 2003). The significant correlations between tutorial quiz scores and scores on critical exam items raises the question of whether critical item scores were higher among tutorial users because of exposure to similar test questions on the quizzes or because the quiz scores indicate mastery of the material.…”
Section: Discussionmentioning
confidence: 90%
“…As in the Varnhagen and Digdon (2002) study, the number of accesses was unrelated to exam scores. This pattern of associations, along with students' favorable ratings of the practice exercises, suggests that it was not just exposure to the content of the tutorials that predicted learning but engaging with problems that required students to apply learned concepts (Karasavvidis, Pieters, & Plomp, 2003). The significant correlations between tutorial quiz scores and scores on critical exam items raises the question of whether critical item scores were higher among tutorial users because of exposure to similar test questions on the quizzes or because the quiz scores indicate mastery of the material.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have shown that the use of computers in classrooms can help increase factual information exchanges and task conceptualization interactions between teachers and students (Karasavvidis et al, 2003). Similarly, Beuckman et al, (2006) stated that technology-enhanced classroom interaction can also improve students' learning as well.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Each segment would then have either a student code or a teacher code assigned depending on the purpose and the speaker. The codes used were modified versions of those used by Karasavvidis et al (2003). Descriptions and examples of these codes can be found in Appendix A.…”
Section: Stagementioning
confidence: 99%
“…Fixed scaffolds consisted of a list of subgoals to be followed during learning. Karasavvidis et al (2003) found that teacher's supportive discourse (akin to adaptive scaffolding) differed when students completed a task on the computer versus paper and pencil.…”
Section: Co-regulation (Teacher-and Student-indirect Regulation)mentioning
confidence: 99%